Personal Learning Environments in Online and Face-to-Face Contexts in Mexican Higher Education - Ramírez-Mera Urith N.; Tur Gemma; Marin Victoria I. (De Gruyter, 2022)
With the introduction of digital technologies in education and the diversification of learning modalities, research has sought to identify the characteristics of each modality in order to develop successful learning. The Personal Learning Environment (PLE) is a developing concept that takes advantage of digital technologies and their implications in different modalities. This research aims to identify how the educational modality contributes to the development of PLEs in higher education. We compared two case studies in online and face-to-face contexts in Mexican higher education through a case survey methodology using a questionnaire and a descriptive statistical analysis of five categories: self-perception, management of information, management of the learning process, communication and learning experience. Results show that online students focus on the use of information management skills and on self-regulation of the learning process, whereas face-to-face students are oriented towards the use of communication skills. In conclusion, we identify two PLE profiles whose main differences arise from the students' learning approaches, one based on social interaction and the other guided by learning aims, two aspects that may contribute to the development of learning strategies for transition between modalities. Finally, we contribute to the support of face-to-face learning in virtual environments and emergency remote teaching.